Seed Weight and Protein Concentration of whole Seed, Cotyledons and Seed Coat of 57 Accessions of Acacia and Prosopis (Mimosaceae) : Phylogenetic and Nutritional Implications - Bukhari, Yahya M. (Indian Forester, 2002)
Phylogenetic and nutritional implications of seed weight and seed protein concentration for 57 accessions of Acacia including A. albida (syn. Faidherbia albida) and Prosopis were discussed. Single seed weights of subgenera Acacia, Aculeiferum, Heterophyllum and, the genera Prosopis and Faidherbia were 96 ± 6, 93 ± 2, 18 ± 3 and, 49 ± 30 and 89 ± 12 mg, respectively. Corresponding cotyledon protein concentrations were 53± 6, 59± 6,38± 1 and, 46 ± 2, and 52 ± 4%. The high seed weight of subgenera Acacia and Aculeiferum are ascribable to the thick seed coat for the former and massive cotyledon for the latter. F. albida resembled subgenus Aculeiferum in seed coat protein concentration and subgenus Acacia in cotyledon protein concentration. Single seed weight and cotyledon protein concentration of P. africana were 15 ± 3 mg and 38%; corresponding average values for the other studied 12 accessions of Prosopis were 40 ± 3 mg and 46 ± 1%. P. africana may not belong to the genus Prosopis. The study proposes that Acacia and Prosopis are possible sources of protein for human use. Subgenus Aculeiferum, including A. albida appeared to have the highest potential in this respect, subgenus Acacia ranked second, the genus Prosopis third and subgenus Heterophyllum last. The data suggest that A. albida fits better in the genus Acacia.